Balancing force field protein-lipid interactions to capture transmembrane helix-helix association - Domański, J; Sansom, MSP; Stansfeld, P; Best, R (American Chemical Society, 2018)
Atomistic simulations have recently been shown to be sufficiently accurate to reversibly fold globular proteins and have provided insights into folding mechanisms. Gaining similar understanding from simulations of membrane protein folding and association would be of great medical interest. All-atom simulations of the folding and assembly of transmembrane protein domains are much more challenging, not least due to very slow diffusion within the lipid bilayer membrane. Here, we focus on a simple and well-characterized prototype of membrane protein folding and assembly, namely the dimerization of glycophorin A, a homodimer of single transmembrane helices. We have determined the free energy landscape for association of the dimer using the CHARMM36 force field. We find that the native structure is a metastable state, but not stable as expected from experimental estimates of the dissociation constant and numerous experimental structures obtained under a variety of conditions. We explore two straightforward approaches to address this problem and demonstrate that they result in stable dimers with dissociation constants consistent with experimental data.